AN OUTLINE AS AN AID IN TEACHING TAX ACCOUNTING FOR PROPERTY. - Brighton, Gerald D. (The Accounting Review, 1957)
Abstract The subject of the tax basis of property and the related subject of gains or losses on disposals are probably the most difficult subjects for most students in an introductory income tax course. Students tend to become rather badly lost among the maze of general rules, exceptions and exceptions to exceptions which cover the various situations. Where appropriate, journal entries are used to help explain the treatments. The outline itself is not complete in this respect. Accordingly, in the class discussion considerable time is spent on this phase. The outline has been given to the students after they have already had one or two days on basis material and have struggled with it for a while. The use of the outline has not produced any startling improvement in student comprehension of the material covered. Many still remain confused. However, there is evidence that on equivalent examinations, grades have been somewhat improved over scores in past semesters before the outline was used.